The Development of Digital Teaching Module Using Flipbook Software Non Test Psychology Assessment - Hasibuan, M Fauzi; Jamila, Jamila; Tanjung, Elisa Fitri (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to develop a digital-based non-test psychological assessment course teaching module, using the Kvisoft Flipbook Maker software, which can display various features, such as audio, images, and videos. This software helps students understand clearly the illustration of the module content. This research method used the development research, with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation) as a reference. The research data were analyzed using descriptive analysis and non-parametric statistical analysis. The findings show that the digital module in the non-test GC psychological assessment course at this university can be used by lecturers to assist lecturers in providing interesting learning to students in higher education.